Simultaneous growth of three-dimensional carbon nanotubes and ultrathin graphite networks on copper - Jang, Lee-Woon; Shim, Jaeho; Son, Dong Ick; Cho, Hyunjin; Zhang, Luman; Zhang, Jie; Menghini, Mariela; Locquet, Jean-Pierre; Seo, Jin Won (NATURE PUBLISHING GROUP, 2019)
A new way to simultaneously grow carbon nanotubes (CNTs) and ultrathin graphite on copper (Cu) foils has been investigated. This one-step growth process yields three-dimensional networks of CNTs on graphitic layers (3D CNTs/G) on Cu foils. Their synthesis conditions and growth mechanism are discussed in detail taking their structural properties into account. Individual CNTs and the 3D CNTs/G networks by means of an in-situ conductive atomic force microscope inside a scanning electron microscope are electrically characterized. Time-resolved photoluminescence demonstrated fast charge transfer and high carrier collection efficiency superior to two-dimensional ultrathin graphite only. Their facile and tunable growth and excellent electrical properties show that the 3D CNTs/G are strongly attractive for various applications such as solar cells, sensors, supercapacitors, photovoltaics, power generation, and optoelectronics.
Keywords: SINGLE-CRYSTAL GRAPHENE; CATALYTIC GROWTH; PERFORMANCE